Answer:
y = -2x - 1
Step-by-step explanation:
Rewrite y + 7 = -2(x - 3) in slope-intercept form (which is y = mx + b):
First, perform the indicated multiplication:
y + 7 = -2x + 6
Combining the constants, we get
y = -2x - 1
This is the desired equation in slope-intercept form. slope is -2 and y-intercept is -1.
Answer: x = 11
Step-by-step explanation:
same as the last question, set them as equal and solve. here's my work:
<em>5x - 1 = 4x + 10</em>
<em>5x - 1 (+ 1) = 4x + 10 (+ 1)</em>
<em>5x = 4x + 11</em>
<em>5x (- 4x) = 4x (- 4x) + 11</em>
x = 11
$207 is the answer, multiply 25 x 36 and 22 x 51 and 3 x 5, then subtract the products from the first two multiplications and then subtract 15 and you get your answer.